Managing fatigue after cancer treatment: development of RESTORE, a web-based resource to support self-management - Foster, Claire; Calman, Lynn; Grimmett, Chloe; Breckons, M.; Cotterell, P.; Yardley, Lucy; Joseph, J.; Hughes, S.; Jones, R.; Leonidou, C.; Armes, Jo; Batehup, Lynn; et al. (Wiley, 2015)
Objective: the aim of this study is to co-create an evidence-based and theoretically informed web-based intervention (RESTORE) designed to enhance self-efficacy to live with cancer-related fatigue (CRF) following primary cancer treatment.